Efficient catalytic hydrogenation of furfural over cobalt-based catalysts with adjustable acidity. (15th April 2023) - Tian, Ye; Chen, Binglin; Yu, Zhendong; Huang, Renjie; Yan, Guihua; Li, Zheng; Sun, Yong; Yang, Shuliang; Tang, Xing; Lin, Lu; Zeng, Xianhai
Graphical abstract: Highly efficient catalytic hydrogenation of furfural over cobalt-based catalysts with adjustable acidity. Highlights: The CoO x /Nb2 O5 was efficient for the production of CPO and CPL. The introduction of Co into Nb2 O5 improved the CO adsorption capacity and changed the B/L acidic sites. CoO x played a crucial role in the hydrogenative ring rearrangement of furan. DFT explicitly elucidated CoO was the primary adsorption site for FF molecule. Abstract: The selective hydrogenation/rearrangement of biomass-derived furfural (FF) to value-added products is critical in the development of renewable chemicals. Herein, a bifunctional catalyst comprising CoOx loaded on Nb2 O5 by the simple wetness impregnation method was constructed, which showed high activity for FF hydrogenation/rearrangement to achieve cyclopentanone (CPO) and cyclopentanol (CPL). The total yield of CPO and CPL was up to 82% with a 20% CoOx /Nb2 O5 catalyst. Catalyst characterization indicated that CoOx was the active site, which is responsible for FF hydrogenation. Furthermore, increasing the catalyst's Brønsted/Lewis acidic sites ratio aided the hydrogenative ring rearrangement. Density functional theory (DFT) verified that CoO has higher adsorption energy than Co3 O4, and intermediate products in the rearrangement process, such as 2-pentene-1, 4–dione (PED), 4–hydroxy-2-cyclopentenone (HCP), and 2-cyclopentenone (2-CEP) are extremely unstable. Furthermore, the polymer formed during the reaction may result in the deactivation of the CoOx /Nb2 O5 catalyst.